Cuentas por pagar de la junta provincial de la Cruz Roja de Los Ríos – Babahoyo, periodo 2023. - Viteri Obando, Karla Nayeli (2024)
This investigation originates from the analysis of the accounts payable of the Provincial Board of the Red Cross of Los Ríos, identifying the outstanding values with different institutions. This organization is a private, non-profit entity dedicated mainly to activities in the health sector, such as the collection and distribution of blood components, in addition to providing humanitarian aid. The general objective is to examine the accounts payable of the Provincial Board of the Red Cross of Los Ríos - Babahoyo, through the review of the financial information presented by the institution in the period 2023. A mixed methodology is used, combining qualitative approaches and quantitative. This method allows both the numerical analysis of accounts payable and their evolution, as well as a deep understanding of the internal processes and dynamics that affect the financial management of the institution. The investigation includes a documentary review of financial statements and an interview with the financial manager. The research highlights the importance of maintaining adequate management of accounts payable to ensure the continuity of the supply of necessary supplies, maintaining a good relationship with suppliers.